IDENTIFICATION OF ANTIBACTERIAL PROPERTY OF DIFFERENT MEDICINAL PLANT EXTRACTS - KUMARI, SWETA; VAISHNAV, VIRENDRA (International Journal of Current Pharmaceutical Research, 2020)
Objective: The objective of this study was to evaluate the antibacterial activity of some plant extracts they are-Curcuma longa, Cinnamomum tamala, Ocimum tenuiflorum, Azadirachta indica, Datura stramonium, Zingiber officinale, Punica granatum and Cinnamomum cassia against Staphylococcus aureus and E. coli. Methods: The evaluation of antibacterial activity for different extracts of each plant was carried out by using the disc diffusion method and by pouring technique to determine the minimum inhibitory concentration (MIC). Results: In the disc diffusion method the plant extracts showed zone of inhibition ranging 02.0 to 16.0 mm against bacteria and In pouring technique plant extracts showed positive control against pure culture of a bacterium and their efficiency in terms of MICs where ranged from 0.2 gm/ml to 0.8 gm/ml. The extracts of Curcuma longa and Cinnamomum tamala shown high efficiency then other plant extracts in terms of zone of inhibition and also in pouring technique less amount of extracts was inhibited the growth of bacteria. Conclusion: This study indicates that extracts of these plants have antibacterial activity against bacteria. This report supports their use in the treatment of infections caused by bacteria.